APLIKASI TRIPTOFAN DAN GLISIN DALAM PAKAN RUCAH SERTA PENGARUHNYA TERHADAP TINGKAT KANIBALISME, PERTUMBUHAN DAN SINTASAN KRABLET KEPITING BAKAU (Scyla serrata) - Suharyanto Suharyanto; Denny I Yudhistira (Jurnal Perikanan Universitas Gadjah Mada, 2012)
The aims of this experiment was to obtain data and information on the percentage of decrease in the levels of cannibalism, growth and survival rate of mud crab crablet (Scyla serrata) by feeding trash mixed with tryptophan and glycine. This research was conducted in the wet lab experimental pond installation at Center of Research and Development of Brackish Water Aquaculture Maranak, Maros for 28 days using 12 aquariums each measuring 80x40x60 m3. Crablets (C-20) from the hatchery were used for this study, measuring 5.3+0.2 mm in width and 0.15+0.02 g in weight. Ten crablets were stocked in each aquarium. The treatments applied were (A): trash ﬁ sh tilapia (Tilapia mosambica), (B): trash ﬁ sh + tryptophan and (C): trash ﬁ sh + glycine, with three replicates per treatment. Feeding dose was 25% of the total biomass crablet while the dose of tryptophan and glycine were 1.0% of the amount of feed given per aquarium. Feeding was done twice a day in the morning and evening. Variables observed were the growth in carapace width, weight, level of cannibalism, survival rate and water quality parameters. The results showed that   adding the amino acids tryptophan and glycine in trash ﬁ sh feed  at 1.0% of total biomass could signiﬁ cantly (P<0.05) suppress the level of cannibalism krablet without affecting the growth rate (weight and width of carapace) and   increase the survival rate of the mud crab krablet.